Timing Analysis of the 2022 Outburst of the Accreting Millisecond X-Ray Pulsar SAX J1808.4-3658: Hints of an Orbital Shrinking - Giulia Illiano; Alessandro Papitto; Andrea Sanna; Peter Bult; Filippo Ambrosino; Arianna Miraval Zanon; Francesco Coti Zelati; Luigi Stella; Diego Altamirano; Maria Cristina Baglio; Enrico Bozzo; Luciano Burderi; et al. (The Astrophysical Journal Letters, 2023)
We present a pulse timing analysis of NICER observations of the accreting millisecond X-ray pulsar SAX J1808.4−3658 during the outburst that started on 2022 August 19. Similar to previous outbursts, after decaying from a peak luminosity of ≃1 × 10 ^36 erg s ^−1 in about a week, the pulsar entered a ∼1 month long reflaring stage. Comparison of the average pulsar spin frequency during the outburst with those previously measured confirmed the long-term spin derivative of ${\dot{ν }}_{SD}=-(1.15\,± \,0.06)× \,{10}^{-15}$ Hz s ^−1 , compatible with the spin-down torque of a ≈10 ^26 G cm ^3 rotating magnetic dipole. For the first time in the last twenty years, the orbital phase evolution shows evidence for a decrease of the orbital period. The long-term behavior of the orbit is dominated by an ∼11 s modulation of the orbital phase epoch consistent with a ∼21 yr period. We discuss the observed evolution in terms of a coupling between the orbit and variations in the mass quadrupole of the companion star.